Toxicodynamic Assessment of Aqueous Neem (Azadirachta indica A. Juss) Seed Extract on Mortality and Carboxylesterase Activity in Key Organs of Bombyx mori L. Larvae - Ajin Rattanapan; Chuthep Phannasri; Chawiwan Phannasri; Patcharawan Sujayanont; Kattinat Sagulsawasdipan (Toxins, 2025)
Botanical insecticides derived from neem (Azadirachta indica A. Juss.) seeds have gained significant interest due to their sustainable characteristics and low environmental impact. However, their use in sericulture remains contentious due to the heightened sensitivity of domesticated silkworms to environmental stressors. This study systematically investigates the toxicodynamic effects of aqueous neem seed extract (ANSE) on fifth instar larvae of Thai multivoltine Bombyx mori L., focusing on larval mortality and carboxylesterase (CarE) enzyme activity in essential detoxification organs. Larvae were exposed to ANSE concentrations ranging from 5 to 50 mg L−1 for up to 72 h. Key findings highlight a pronounced dose- and time-dependent increase in mortality, with an accurately determined LC50 value of 17 mg L−1 at the longest time exposure, accompanied by mortality rates reaching approximately 83% at the highest concentration tested, indicating considerable susceptibility. Additionally, notable and distinct organ-specific responses were observed, with significant inhibition of CarE activity in the midgut contrasting with elevated activities in the fat body and Malpighian tubules. These differential enzymatic responses reveal previously undocumented adaptive detoxification mechanisms. Consequently, the study advocates cautious and regulated application of neem-based insecticides in sericulture, recommending precise management of concentrations and exposure durations according to silkworm strain sensitivities to ensure optimal silk production.